The impact of service quality attributes of beauty parlors towards customer loyalty through customer satisfaction and trust - Maudy Mikha Maria Tambayong; Pauline h. Pattyranie tan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine examine the positive impact of customer loyalty in a beauty parlor through customer satisfaction. The survey method was carried out in research using a questionnaire. This research is a random sampling research with a total of 144 Sister’s Beauty Studio customers as respondents. The data analysis used the PLS-SEM approach with the help of the SMART-PLS program. The result showed tangibility, reliability, assurance, empathy and responsiveness did have positive impacts on customer satisfaction. Furthermore, the research also handed out customer satisfaction has a positive impact on customer loyalty and hence customer trust.